The Effects of Music Therapy-Singing Group on Quality of Life and Affect of Persons With Dementia: A Randomized Controlled Trial - Cho, Heeyoun Kim (Frontiers in Medicine, 2018)
Dementia is a clinical syndrome that is progressive and degenerative, affecting memory, behavior, emotion and personality. Persons with dementia often experience deterioration of cognitive ability, as well as various behavioral and psychological disturbances, which significantly contribute to reduced quality of life and emotional well-being. The demand for long-term care continues to rise rapidly and it is therefore critical to develop effective strategies and evidence-based interventions to improve the quality of life for persons with dementia. Music therapy has drawn attention as a promising non-pharmacological approach for persons with dementia. A variety of music interventions including singing and listening to music have been widely applied for dementia care not only by music therapists, but also by other healthcare professionals. There are, however, little research studies that compare possible effects of music therapy interventions with those of music-based approaches on dementia care. The purpose of the current study was to investigate the short-term effects of a music therapy-singing group and compare them with those of a music medicine-listening group and a control-TV group, on quality of life and affect of persons with dementia at a long-term care facility. The music therapy-singing group was facilitated by a music therapist, whereas the music medicine-listening and the control-TV group were led by nursing home activity staff. Fifty-two participants, whose ages range from 63 to 99 years old, were randomly assigned to one of the three groups, and thirty-seven participants completed the interventions. The participants in each group were engaged for a 40-minute session twice a week for four consecutive weeks. Quality of life was measured at the baseline and after the last session. Only the music therapy-singing group demonstrated significant improvements when compared to the other groups. Positive and negative affect were measured at three points, including pre and post the first, fourth and eighth sessions. Only the music therapy-singing group significantly increased positive affect scores and decreased negative affect scores. The findings of the current study suggest that music therapy with active singing may be an effective non-pharmacological intervention in improving quality of life and affect of persons with dementia at long-term care settings.